STRENGTHENING SANTRI CHARACTER EDUCATION THROUGH THE MANAGEMENT OF KITAB NUSANTARA INSTRUCTION - Fuad Fahmiy; Subaidi Subaidi; Sukarman Sukarman (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2026)
This study aims to analyze the management of Kitab Nusantara learning as an instrument for strengthening the character education of santri. This research uses library research with a descriptive-analytical approach. Data were collected through documentation studies and analyzed using qualitative content analysis. The findings show that structured educational management through planning, organizing, implementation, and evaluation can transform classical Islamic texts into practical character formation instruments. The Amanati program through Kitab Huququl Arham learning strengthens the values of respect and obedience to parents (birrul walidain), empathy, compassion (rahmah), social responsibility, discipline, and integrity. The integration of intensive mentoring, family-based implementation during holidays, community daurah assignments, and reward-punishment systems encourages the transformation of moral knowledge into moral action. Thus, systematic management of Kitab Nusantara learning contributes significantly to creating santri with strong religious and social character.